The Impact of Climate Finance and Corporate Sustainability on Firm Value in Multinational Companies in Indonesia - Loso Judijanto; Edy Arisondha (Westscience Press, 2026)
This study examines the impact of climate finance and corporate sustainability on firm value in multinational companies operating in Indonesia. Using a quantitative approach, data were collected from 125 respondents through a structured questionnaire measured on a Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both direct and indirect relationships among variables. The results indicate that climate finance has a positive and significant effect on firm value, while corporate sustainability demonstrates a stronger positive influence. Furthermore, climate finance significantly affects corporate sustainability, indicating its role as a key driver of sustainability practices. Mediation analysis reveals that corporate sustainability partially mediates the relationship between climate finance and firm value, with a significant indirect effect. These findings suggest that the value of climate finance is maximized when it is effectively translated into sustainability practices. The study contributes to the literature by providing empirical evidence from an emerging market context and highlights the importance of integrating financial and sustainability strategies to enhance firm value. Practical implications emphasize the need for managers and policymakers to strengthen sustainability-oriented financial mechanisms to support long-term corporate performance and environmental responsibility.